Studi Kritis Tentang Nikah Sirri Antara Hukum Islam dan Perlindungan Hukum Negara (International Forum of Researchers and Lecturers, 2023)
Unregistered marriage (nikah sirri) is a phenomenon that has attracted the attention of many, both from the perspective of Islamic law and positive law in Indonesia. This study aims to critically examine nikah sirri, including its definition, legal basis, and the social impacts it causes. Using a qualitative approach, this research collects data from various sources, including legal literature, interviews, and case studies. The results show that although nikah sirri is recognized under Islamic law, its practice often conflicts with the state's legal protection and can have negative consequences, especially for women and children. The issue of nikah sirri is complex as it involves two different legal domains—religious law and state law. On the one hand, nikah sirri may be considered valid according to Islamic principles if it fulfills the requirements and pillars of marriage. On the other hand, since it is not recorded in the state’s administrative system, it raises several legal and social issues, particularly regarding the protection of women's and children's rights. Therefore, a well-structured problem formulation is needed to thoroughly explore the conflicts and gaps between Islamic law and positive law in addressing the practice of nikah sirri.